Produção de éster etílico via reação in situ a partir da biomassa da Chlamydomonas reinardtii - Rodrigues, Simone Cristina (2016)
For some years, the environment has been one of the main concerns of the global population. The need for alternative sources and ecologically friendly practices, as well as biofuels, is an option that fits sustainable development. In search for high oil content raw materials, microalgae have been considered as a useful and promising source of biodiesel. Thus, the paper aimed to evaluate the production of ethyl esters via in situ reaction of the biomass obtained in the cultivation Chlamydomonas reinhardtii microalgae, to determine the best cultivation medium based on productivity, to develop microalgae cultivation for biomass production, to determine lipid content, the in situ reaction for ethyl esters production characterize and quantify the obtained esters. From the results obtained with the extraction, it was observed that the characteristics of the solvents can promote the lipid extraction of the biomass. Chlamydomonas reinhardtii microalgae was cultivated in TAP medium, with controlled artificial light and temperature. Then, there was the recovery of the biomass, which analyzed for chlorophyll a and b proteins and total carbohydrates and finally, the lipid content in the biomass was obtained and quantified by analyzing the ethyl esters present by gas chromatography. The chlorophyll, protein and carbohydrate contents were: 54.136 mg / L -1, 29.39% and 14.92%, respectively, and the highest lipid content was 4.03%. The yield of the biomass culture was of 0.646 gL-1. From the results obtained with the extraction, it was observed that, the polarity of the solvent influences the productivity of lipids. In the production of esters the predominant in situ reaction is the temperature and reaction time, with the highest yields at 60ºC (1.504 mg of ester/g of biomass in 30, 1.518 mg of ester/g of biomass in 45 and 1.509 mg of ester/g of biomass in 60 minutes). In the production of esters, the factor analysis showed that there was interaction between temperature and time, on average, the best yields in number of C15 and C16 cetanes being C16 (76.97% at 30°C, 58.21% at 45°C, 64.05 % In 60°C and 56.79% in 75°C) profile of esters obtained, suitable for the production of biodiesel. The obtained results showed that the Chlamydomonas reinhardtii microalgae biomass presents potential for biodiesel production, when cultivated under the conditions tested in this study.